The epidemiology of thyroid cancer in the twentieth and early twenty-first century in Ukraine and Zaporizhzhia region - O. M. Sydorenko; M. O. Sydorenko; M. P. Tymoshev (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Abstract